Forty -seventeen - Moorhouse, Frank, 1938- (Faber and Faber, 1989)
What could he tell her now, now that he was forty and she was no longer 17? He is a failed writer turned diplomat, an anarchist learning the value of discipline. He moves in a world which takes him from the Australian wilderness to the conference rooms of Vienna and Geneva; from the whore-house to warzone he feels the pull of the genetic spiral of his ancestry. At the sharp axis of his mid-life he scans the memorabilia of his feelings in the hope of giving answers.